Controle de qualidade, medição de dose glandular média e protocolo de rotina para tomossíntese digital mamária - Messias, Pricila Cordeiro (2016)
In Brazil, breast cancer is the most common and the leading cause of death among women; in 2015, 57,120,000 new cases. Digital Breast Tomosynthesis (DBT) reduces the effects of overlapping breast tissue, offering a better characterization of mammographic findings and decreasing the need of additional views. The recent introduction of DBT in clinical practice requires, in order to maintain the dose requirements and image quality, aside from routine Quality Control (QC) procedures and monitoring the Mean Glandular Dose (MGD) also a qualified technical team to perform the procedure. The practice of monitoring the image quality and the radiation dose is a solution to continuously ensure high quality diagnostic radiology exams. Few studies related to CQ TDM in Brazil, and national and international specific protocols have not been established, Thus, QC tests used are based on those used by the National Health Service Breast Screening Programme (NHSBSP), European Reference Organization for Quality Assured Breast Screening and Diagnostic Service (EUREF), American Association of Physicists in Medicine (AAPM), International Atomic Energy Agency (IAEA). This study proposes and presents the results of the QC tests and DGM for mammography and TDM, and routine protocol for TDM tests. The QC tests for TDM were performed according to the manufacturer's recommendations, of Portaria 2898/13 and international protocols. The Routine Protocol was elaborated aiming to resolve the most frequent doubts of the technical team, as well as optimize the room examination. In order to certify the quality of the diagnostic image for all thicknesses, a imagine quality test from the standard simulator of American College of Radiology (ACR) was performed. In the DGM evaluation, all values mammography and TDM remained in accordance with the reference range used except for 20 mm TDM. For all other QC tests, the results remained in accordance with the reference limits. The results obtained in the assessments emphasize the importance of quality control applied properly in obtaining the imaging process, ensuring low dose and good image quality, fulfilling the ALARA principle.